TARI PIRING DALAM PERTUNJUKAN RANDAI DI SANGGAR PALITO NYALO KOTO PANJANG KECAMATAN PAUH PADANG SUMATERA BARAT - Sapitri, Dwi Ranti; Risnawati, Risnawati; Gusti, Adriana (Institut Seni Indonesia Padangpanjang, 2023)
The purpose of this study was to determine the form of the Plate Dance in the Randai Performance at the Palito Nyalo Studio, Koto Panjang District, Pauh District, Padang City, West Sumatra. This study uses a descriptive qualitative method, which is to describe and describe the data that is seen in the real field. How to get data by literature study and field study. Theories and opinions used in studying the Forms of the Plate Dance in the Randai performance consist of form theory by Y. Sumandiyo Hadi. Performance theory by Sal Murgianto. The form of the Piring Dance in the Randai performance at the Palito Nyalo Studio is related to dance elements, namely motion, music, costumes, props, and the venue. Furthermore, the Plate Dance in the Randai show has a unique way of breaking plates using four ways, namely: Forehead, elbows, knees, and soles of the feet which are located at the end of the show. This Piring dance performance prioritizes a form of entertainment which essentially eliminates boredom or changes the atmosphere in a randai show.